Optimal biscuit baking condition and characterization of the biscuit physiochemical, functional, antioxidant, anti-nutrient and textural properties - Elias Ture; Meseret Bekele (Cogent Food & Agriculture, 2024)
The study aimed to investigate the optimal baking condition using optimal custom design of Design expert software, and the properties of the optimized and control biscuits were determined. Sorghum, grass pea, and orange-peel flour were blended with three different proportions to prepare sorghum-based biscuits. The study was based on three factors in which the blend ratio was used as a categorical factor. The factors were baking temperature (180 °C, 200 °C, 220 °C), baking time (15 min, 20 min, 25 min) and blend ratio (B1 = (80:15:5), B2 = (65:25:10) and B3 = (50:35:15)). The variance of the data was analyzed using Minitab statistical software (version 21). The results showed that the process parameters had a significant (p < .05) effect on the characteristics of the biscuits. The results of chemical analysis showed that biscuit baked with blend one (B1 = (80% S, 15% G, 5% O) was the optimized product baked at a baking temperature of 180 °C and time of 15 minutes. Compared to baking temperature and time, blend ratio resulted in superior biscuit quality in terms of chemical characteristics, and lower biscuit acceptance in terms of sensory characteristics.